FACTORS INFLUENCING CONSUMERS' ENVIRONMENTALLY SUSTAINABLE FOOD CONSUMPTION IN BANGALORE (International Journal of Food and Nutritional Sciences, 2021)
Abstract: The challenge of convincing people to change their eating habits toward more environmentally sustainable food consumption (ESFC) patterns is becoming increasingly pressing. Food preferences, choices and eating habits are notoriously hard to change as they are a central aspect of people’s lifestyles and their socio-cultural environment. The main objective of the study is to explore the Factors influencing Consumers' Environmentally Sustainable Food Consumption in Bangalore. Cluster sampling was adopted for the purpose. Bangalore City was chosen as major study area. This region was divided into 4 clusters being north, south, east, west. A total of 892 consumers having a habit of consuming environmentally sustainable food products as study population. The data has been collected through issuing structured questionnaire. Regression analysis was used as statistical tool. It is found that, the unique contribution of the variables such as eating habits, followed by leading quality of life, environmental concern, consumer knowledge, consumer lifestyle, importance to local food and human health, product freshness, plant-based diet, nutrition, product taste, signal of social status, influence of reference groups in predicting environmentally sustainable food consumption by consumers in Bangalore city. It is also found that, the unique contribution of the variables such as company marketing strategies, followed by product price, availability of products, quality of the product, advertising appeal, government encouragement for the companies and companies environmental concern, social concern, promoting sustainable food products in predicting environmentally sustainable food consumption by consumers in Bangalore city.